2018
DOI: 10.1111/eva.12696
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the deep‐sea mussel Bathymodiolus platifrons (Bivalvia: Mytilidae) in the Northwest Pacific

Abstract: Studying population genetics of deep‐sea animals helps us understand their history of habitat colonization and population divergence. Here, we report a population genetic study of the deep‐sea mussel Bathymodiolus platifrons (Bivalvia: Mytilidae) widely distributed in chemosynthesis‐based ecosystems in the Northwest Pacific. Three mitochondrial genes (i.e., atp6, cox1, and nad4) and 6,398 genomewide single nucleotide polymorphisms (SNPs) were obtained from 110 individuals from four hydrothermal vents and two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 73 publications
3
55
0
Order By: Relevance
“…The eastward spread is stronger in both winter and spring (You et al, 2005). Previously, by using genomewide SNP markers, Xu et al (2018) revealed a limited gene flow of the deep-sea mussel Gigantidas platifrons (previously known as Bathymodiolus platifrons) between the SCS and the OT. However, G. platifrons and S. crosnieri have different lifehistory traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The eastward spread is stronger in both winter and spring (You et al, 2005). Previously, by using genomewide SNP markers, Xu et al (2018) revealed a limited gene flow of the deep-sea mussel Gigantidas platifrons (previously known as Bathymodiolus platifrons) between the SCS and the OT. However, G. platifrons and S. crosnieri have different lifehistory traits.…”
Section: Discussionmentioning
confidence: 99%
“…Bathymodioline mussels produce planktotrophic larvae that take almost a year to develop, and their dispersal ability is largely influenced by the upper or surface currents (Arellano and Young, 2009). Consequently, the limited larval exchange of G. platifrons between the two sides of the Luzon Strait is suggested to be achieved by the looping path of the Kuroshio Current, which flows into the SCS via the middle part and exits via the northern part of the Luzon Strait (Nan et al, 2011), as well as by the North Pacific Intermediate Water (NPIW; Xu et al, 2018). In contrast, S. crosnieri produces large (2 mm) oil-rich eggs and equally oil-rich lecithotrophic larvae (Miyake et al, 2010;Nakajima et al, 2018), and its dispersal is expected to mainly occur within the middle and deep layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it was rst discovered in 1987 in Sagami Bay, Gigantidas platifrons (formerly named as Bathymodiolus platifrons) has been found to be dominant in cold seeps and hydrothermal vents of Okinawa Trough and Formosa Ridge of the South China Sea [29][30][31]. It was found that G. platifrons only harbored MOBs in their bacteriocytes, making them an ideal model for investigating the immune response against symbionts.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was rst discovered in 1987 in Sagami Bay, Gigantidas platifrons (formerly named as Bathymodiolus platifrons) has been found to be dominant in cold seeps and hydrothermal vents of Okinawa Trough and Formosa Ridge of the South China Sea [29][30][31]. It was found that G. platifrons only harbored MOBs in their bacteriocytes, making them an ideal model for investigating the immune response against symbionts.…”
Section: Introductionmentioning
confidence: 99%